PENGARUH PENAMBAHAN KAPASITOR PADA SISTEM PENGAPIAN AC (ALTERNATING CURRENT) DAN VARIASI BUSI TERHADAP EMISI GAS BUANG PADA SEPEDA MOTOR 4 TAK 100 CC - Supriyadi Supriyadi; Joko Suwignyo; Fuad Abdillah; Fahmy Zuhda Bahtiar (Ivet University, 2025)
This research aims to determine the effect of adding capacitors and variations in spark plugs on the Exhaust Gas Emission content of the Honda Supra X 100cc motorbike. This research method uses an experimental method with descriptive statistics. The object used in this research is a 100cc Supra The place of research was carried out at the PVTMO Ivet Semarang Automotive Workshop. The technique used in collecting data is conducting experiments by testing the objects to be studied and recording the necessary data. Data analysis in this research uses descriptive statistics, namely describing or describing the data that has been collected as it is without making general conclusions or generalizations. The resulting data includes the amount of CO, HC, CO2, O2, lambda, and AFR. The research results showed that the highest CO gas content was produced by Spark Plug Racing using additional capacitors with an average value of 6.80%. Meanwhile, the lowest CO gas content is created by original or standard spark plugs without using additional capacitors with an average value of 5.93%. Meanwhile, the highest HC was produced by Racing Spark Plugs using additional capacitors with an average value of 485 ppm, almost the same as that produced by original spark plugs with the addition of capacitors. Meanwhile, the lowest HC gas content is produced by original or standard spark plugs without using additional capacitors with an average value of 378 ppm.